Pengaruh Servicescape Terhadap Minat Beli Ulang (Studi Pada Konsumen Giggle Box Café & Resto Cihampelas Walk Bandung) - Nadya Yunisya; Ai Lili Yulianti (Jurnal Computech & Bisnis (e-Journal), 2017)
This research was conducted to determine the influence of servicescape on the customer repurchase intention in Giggle Box Café & Resto Bandung. The method used is the quantitative methods with this type of research is a study of the causal and descriptive. Giggle Box Café & Resto Cihampelas Walk Bandung is a restaurant in Bandung City, this restaurant served western food and Indonesian food. The sampling that used in this research is non-probability sampling with the type is accidental sampling. The number of respondents are 100 respondents who consume Giggle Box Café & Resto Cihampelas Walk. Data analysis technique that being used is multiple linear regression analysis. In this research, servicescape is in good category and repurchase intention is in passable category. Based on the results of hypothesis testing simultaneously, servicescape variables influence positively and significantly to consumer repurchase intention Giggle Box Café & Resto Cihampelas Walk Bandung. Based on the results of partial hypothesis test, obtained that ambient condition, spatial layout and functionality, and sign, symbol, and artifact have no effect positively and significantly to consumer repurchase intention. Based on the coefficient of determination is obtained that the influence of servicescape variables on the consumer repurchase intention is 22,9% and 77,1% of rest is affected by other factors such as quality of service and etc that were not examined in this research.Keywords: repurchase intention, servicescape, consumer behavior.